Unraveling employee life satisfaction: exploring the impact of psychological contract breach, self-efficacy, mental health, and abusive supervision, with work engagement and job satisfaction as mediators - Md. Abu Issa Gazi; Abdullah Al Masud; Md. Abdul Kaium; Mohammad Bin Amin; Prince Mahmud; Abdul Rahman bin S Senathirajah; Masuk Abdullah (Cogent Psychology)
This study aims to investigate the effects of psychological contract breach, self-efficacy, mental health, and abusive supervision on employee life satisfaction. Additionally, it examines how work engagement and job satisfaction mediate these effects. Analyzing data from 380 corporate employees in Bangladesh, a survey methodology was employed to test the claimed associations using structural equation modeling (SEM). Self-efficacy and mental health boost work, life, and job satisfaction. Unsurprisingly, abusive supervision and psychological contract breaches do not affect work engagement. Work engagement and job satisfaction affect psychological contract breach, self-efficacy, mental health, abusive supervision, and life satisfaction. By examining how psychological contract breach, self-efficacy, mental health, and abusive supervision affect employee life satisfaction, this study advances understanding level. The study investigates these factors in a developing country’s corporate sector. Employees’ work engagement, job satisfaction, and life satisfaction can be improved by improving self-efficacy, mental health, and psychological contract breaches. These elements should be included in HR policy and staff development programs to create a healthier and more productive workplace.